RESEARCH OF INSOLUBLE RESIDUE OF CARBONATE ROCKS OF ZARICHNA AREA IN DNIPROVO-DONETSK BASIN BY THE COMPLEX MEHODS - Vyzhva, S.; Gozhik, A.; Filipaki, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
These two methods determine a insoluble residue сhemical and X-ray fluorescent methods research carbonate rocks of collectors. Presented and compared, the results, the dependence was built by two methods research Zarechnaya core area.